2019
DOI: 10.1016/j.apcatb.2019.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus modification to improve the hydrothermal stability of a Cu-SSZ-13 catalyst for selective reduction of NOx with NH3

Abstract: Phosphorus is introduced to modify the Cu-SSZ-13 catalyst via incipient wetness impregnation, with P/Cu-SSZ-13 = 1 and 2 wt.%, and Si/Al = 4, for selective catalytic reduction of NOx with NH 3 . N 2 physisorption and XRD results show the incorporation of phosphorus as phosphate acid enhanced the hydrothermal stability of Cu-SSZ-13 significantly, during hydrothermal aging in 10 vol.% H 2 O/air at 750 °C for 16 h. NMR and Raman results suggest that phosphate ions migrate and coordinate with the framework-bonded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 72 publications
4
51
1
2
Order By: Relevance
“…The Cu-SAPO-34 shows a robust HTA stability when aged at high temperatures, which maintains a high SCR activity even aer HTA at 850 C. 5 P in SAPO-34 has been proposed critical to stabilize the CHA type framework in hydrothermal condition. 14 Cu-zeolites with a combination of two zeolite structures showed enhanced HTA stability over single catalyst. For example, Cu-ZST-1 (AFX/CHA), 15 Cu-SAPO-34/5 (CHA/AFI), 16 and Cu-OFF/CHA 17 composites exhibited improved hydrothermal stability than the individual component.…”
Section: Introductionmentioning
confidence: 99%
“…The Cu-SAPO-34 shows a robust HTA stability when aged at high temperatures, which maintains a high SCR activity even aer HTA at 850 C. 5 P in SAPO-34 has been proposed critical to stabilize the CHA type framework in hydrothermal condition. 14 Cu-zeolites with a combination of two zeolite structures showed enhanced HTA stability over single catalyst. For example, Cu-ZST-1 (AFX/CHA), 15 Cu-SAPO-34/5 (CHA/AFI), 16 and Cu-OFF/CHA 17 composites exhibited improved hydrothermal stability than the individual component.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have conducted phosphorus-poisoning investigations over catalytic components, such as the DOC, and selective catalytic reduction (SCR) catalysts. 12,[21][22][23][24] Kröger et al 25 have found that phosphorus poisoning results in a decrease in the specific surface area and pore volume in DOCs and an increase in the average pore size of the catalysts. Toops and coworkers 18 have studied the deactivation mechanism of Pt/CeO 2 /Al 2 O 3 upon phosphorus poisoning, where phosphorus primarily in the form of aluminum phosphate was found to accumulate mainly at the front of the DOC.…”
Section: Introductionmentioning
confidence: 99%
“…Selective catalytic reduction with ammonia (NH 3 -SCR) has been successfully developed as a promising technology for reducing NOx emitted in combustion gas emissions from automotive sources [1][2][3]. Cu-SSZ-13, with superior activity and durability, has been generally considered as the predominant commercial SCR catalyst applied in North American, European and Chinese diesel vehicles [4][5][6].…”
Section: Introductionmentioning
confidence: 99%